Characterization of natural killer and T cells in bronchoalveolar lavage and peripheral blood of sarcoidosis patients - Bergantini, Laura; d’Alessandro, Miriana; Del Zotto, Genny; Marcenaro, Emanuela; Bargagli, Elena (Frontiers in Immunology, 2023)
The aim of this study was to investigate the frequency and phenotype of natural killer (NK) cells and T cells in the bronchoalveolar lavage fluid and peripheral blood of patients with pulmonary sarcoidosis in order to discriminate the differential status of NK and T cells in these two compartments. The analysis revealed that CD56brightCD16neg resulted higher in BAL than PB of sarcoidosis and healthy subjects, while CD56dimCD16+ showed a different proportion between BAL and PB of both Sarcoidosis patients and HC. Moreover, in comparison with autologous PB, BAL was characterized by a higher expression of activated NK cell marker NKp44, CD69 and CD25. In addition, significantly elevated levels of PD-1+ NK cells in the BAL of patients were observed. Regarding the maturation of CD4 and CD8, an increase of Effector Memory T cells (TEM) was reported in BAL compared to PB A better characterization of these cells may lead to a better understanding of the mechanisms behind the inflammatory process in sarcoidosis.